Adiponectin receptors activation performs dual effects on regulating myogenesis and adipogenesis of young and aged muscle satellite cells. Issue 3 (9th December 2022) - Liu, Shibo; Liu, Hanghang; Liu, Yao; Zhang, Ju; Liu, Zhikai; Zheng, Zizhuo; Luo, En
Abstract: Objectives: Skeletal muscle mass and function deteriorate with ageing. Adiponectin receptors (APNrs), mainly activated by adiponectin, participate in various physiological activities and have varying signalling pathways at different ages. This study aimed to explore whether discrepant performance exists in APNr activation regulating young and aged muscle satellite cells (MUSCs) and whether age‐related muscle dysfunction could be alleviated upon APNr activation. Methods: The gastrocnemius muscle phenotype was observed in male mice aged 2 and 18 months. An APNr agonist (AdipoRon) was used in vitro and in vivo to investigate the changes in cell biological behaviours and whether muscle dysfunction could be retarded after APNr activation. Results: Aged mice exhibited decreased muscle mass and increased fat infiltration. APNr activation inhibited C2C12 cells and young MUSCs (YMUSCs) proliferation but showed no obvious effect on aged MUSCs (AMUSCs). Moreover, APNr activation inhibited the migration of both YMUSCs and AMUSCs. Interestingly, APNr activation hampered the myogenic differentiation but advanced the adipogenic differentiation of YMUSCs, yet exact opposite results were presented in AMUSCs. It was demonstrated that Wnt and PI3K signalling pathways may mediate the phenotypic differences. Furthermore, in vivo experiments verified that APNr activation ameliorated age‐related muscle atrophy and excessive fat infiltration. Conclusions: APNr activation exerted dual effects on the regulation of myogenesis and adipogenesis of YMUSCs and AMUSCs and rescued age‐related skeletal muscle dysfunction. Abstract : Adiponectin receptor (APNr) activation had different effects on myogenic and adipogenic differentiation between aged and young skeletal muscle satellite cells (MUSCs), owing to the different reactions of PI3K and Wnt signalling pathways in young and aged states. Activation of APNr could promote the myogenic differentiation of aged MUSCs and inhibit their adipogenic differentiation, and further improve age‐related skeletal muscle atrophy and reduce fat accumulation.